The Effectiveness of IPS-based Contextual Learning to Improve Students Character - Warsito, Warsito; Asrowi, Asrowi; Mulyoto, Mulyoto; Anitah, Sri (International Journal of Active Learning, 2016)
This research aims to 1) find the reasons so that the learning of contextual-based IPS is effective to increase the student's character, 2) describes the effectiveness of IPS-based contextual learning to improve students ' character, 3) compare the effectiveness of IPS-based contextual learning with learning conventional IPS in an attempt to improve the character of students. This research uses qualitative and quantitative paradigms (mixed methods). The population in this research is grade VIII SMP Negeri in Surakarta (solo) and Boyolali district in Sukoharjo, Karanganyar, Wonogiri, Sragen, Klaten and. Total sample overall as much as 828 students incorporated in 26 classes, classes of experimental group 13 (414 students) and 13 classes of control group (414 students). Data collection technique using the test, questionnaire, interview, observation, and documentation. Data analysis techniques with different test that begins with a test of its homogeneity and normality test.How to CiteWarsito, W., Asrowi, A., Mulyoto, M. & Anitah, S. (2016). The Effectiveness of IPS-based Contextual Learning to Improve Students Character. International Journal of Active Learning, 1(1).